2020
DOI: 10.20473/mgi.v15i3.219-224
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Related Factors Among Female Students at Vocational High School Bekasi, Indonesia

Abstract: Hypertension is one of non-communicable diseases which prevalence is high in Indonesia, not only among adult and elderly but also among adolescent. Hypertension can be caused by various factors including fat intake, fi ber intake and nutritional status. The purpose of this study was analyze the correlation of fat intake, fi ber intake, and obesity with hypertension among female students at Vocational high school, Bekasi, Indonesia. This was a cross sectional study among 255 female students who were selected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
1
3
0
3
Order By: Relevance
“…The results of this study are in line with research conducted by (Syah et al, 2020), namely there are differences in the attitudes of respondents before and after in the intervention group, but there is no difference in attitudes of respondents before and after in the control group. And research conducted by (Margaretha, 2015) showed that there were differences in attitudes in the treatment group and no differences in attitudes in the control group.…”
Section: The Effect Of Pocket Books As a Media For Nutrition Counseli...supporting
confidence: 90%
“…The results of this study are in line with research conducted by (Syah et al, 2020), namely there are differences in the attitudes of respondents before and after in the intervention group, but there is no difference in attitudes of respondents before and after in the control group. And research conducted by (Margaretha, 2015) showed that there were differences in attitudes in the treatment group and no differences in attitudes in the control group.…”
Section: The Effect Of Pocket Books As a Media For Nutrition Counseli...supporting
confidence: 90%
“…Sama halnya dengan hasil yang didapatkan Ravi tahun 2016 yang dikutip dalam penelitian (PUTRI, 2019) ialah konsumsi natrium diatas 2 gram setiap harinya merupakan penyebab adanya kenaikan tekanan darah sistolik. Didukung juga dengan penelitian (Syah et al, 2020) yang memberikan hasil bahwa remaja yang mempunyai asupan lemak tinggi memiliki hubungan dengan hipertensi, hal ini biasanya dipicu dengan gaya hidup tidak sehat khususnya konsumsi makanan serta minuman berkalori tinggi. Selanjutnya remaja yang memiliki natrium berlebih, lebih beresiko terkena hipertensi dibandingkan remaja yang memiliki asupan natrium cukup .…”
Section: Pembahasanunclassified
“…Selaras dengan penelitian yang dilakukan (Suryawan, 2018) menunjukkan berat badan atau IMT dengan kategori obesitas, lebih memiliki resiko untuk terena hipertensi namun tidak menutup kemungkinan untuk remaja yang ber IMT normal. Begitu pula pada penelitian Volume 2, Nomor 3, September 2021 ISSN : 2774-5848 (Online) ISSN : 2774-0524 (Cetak) yang dilakukan oleh (Syah et al, 2020) obesitas sangat erat kaitannya dengan kejadian hipertensi, hasil juga menunjukkan hubungan antara obesitas dengan hipertensi pada remaja, dimana obesitas dapat dipicu oleh asupan energi, lemak, karbohidrat yang terlalu berlebih, sering mengkonsumsi makanan cepat saji, memiliki aktivitas fisik yang ringan serta terbiasa untuk tidak sarapan pagi. Remaja yang memiliki IMT berlebih atau dapat dikatakan obesitas akan lebih beresiko terkena hipertensi.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…The results showed that there was a relationship between fat intake (p=0.011) and obesity (p<0.01) on hypertension in adolescents. Routine blood pressure checks and restriction of fat intake are needed to reduce the risk of hypertension in adolescents (Syah et al, 2020). Prevention of hypertension risk factors is effective early on to maintain normal blood pressure and prevent the development of high blood pressure.…”
Section: Introductionmentioning
confidence: 99%